Відновлення правої частини рівняння дифузії з дробовою похідною за часом - Лопушанська, Г. П.; Lopushanska, H. P. (Видавництво Львівської політехніки, 2017)
Доведено коректнiсть оберненої задачi про знаходження пари функцiй: розв’язку u першої кра- йової задачi для лiнiйного рiвняння дифузiї D t u 􀀀 uxx = g(t)F0(x) + h(x; t) з регуляризованою дробовою похiдною порядку 2 (0; 2) за часом в обмеженiй цилiндричнiй областi та функцiї F0(x) за додатково заданих значень u в фiксований момент часу.

We prove the correctness of the inverse problem on determination of a pare of functions: the solution u of the first boundary value problem for linear diffusion equation D t u 􀀀 uxx = g(t)F0(x) + h(x; t) with regularized fractional derivative of order 2 (0; 2) with respect to time on bounded cylindrical domain and function F0(x). Given values of u in a fixed time moment is as the over-determination condition.
On determination of the right-hand side of fractional diffusion equation
Keywords: похідна дробового порядку; обернена крайова задача; інтегральне рівняння; функцiя Мiттаг–Леффлера; fractional derivative; inverse boundary value problem; integral equation; Mittag–Leffler function; 517.95